Basidiomycota Mushroom Diversity in West Kalimantan, Indonesia: A Literature Review and Their Potential as a Senior High School Biology Learning Resource - Faturrahman, Mas Akhbar; Asyrofi, Harun; Sandra, Klaudia Mareta; Wahyuni, Dina; Ningsih, Kurnia; Afandi, Afandi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The level of diversity of Basidiomycota mushrooms is very high. The very high diversity of Basidiomycota mushrooms can also be found in West Kalimantan Province. This diversity is an interesting thing to be used as a source of biology learning. This study aims to analyze the potential diversity of Basidiomycota mushrooms in West Kalimantan as a source of learning biology, especially in the material of Fungi roles. This research is classified as qualitative research and consists of two stages. The first stage is a literature study aimed at collecting data on the diversity of Basidiomycota mushrooms in West Kalimantan, while the second stage is an analysis of learning resource requirements. The first stage was discovering 187 species of Basidiomycota mushrooms found in West Kalimantan. The result of the second stage is that the diversity of Basidiomycota mushrooms in West Kalimantan meets six learning resource requirements that must be met, namely clarity of the potential availability of objects and problems raised, suitability for learning objectives, clarity of targets and their designation, clarity of information disclosed, clarity of exploration guidelines, and clarity of the results to be achieved. Based on the research that has been done, the diversity of Basidiomycota mushrooms in West Kalimantan has potential as a biology learning resource on the Fungi roles material.